ANALISIS PENGELOLAAN USAHA KARYAWAN DALAM MEMPENGARUHI PERSONAL BALANCED SCORECARD PERUSAHAAN TV BERBAYAR - Iqbal, Iqbal Ramadhan; Purwoko, Bambang; W. Sumarlin , Antonius W. Sumarlin (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2017)
The purpose of this research is to analyze by function business influence sales force employees advertising workers at the level of account executive of personal balanced scorecard pay-tvcompany. The research was conducted in Indonesia's pay-tv industry, PT MNC with its MNC Channels business unit. The sampling technique was done by accidental sampling. Analysis of data use the Structural Equation Model (SEM) with data processing using SMART PLS3. The result showed that there is a positive connection between effort and personal balanced scorecard. The relationship indicates that working hard, work smart, open to receive advice, and results clear can increase the personal balanced scorecard.The higher effort was the higher personal also balanced scorecard salesperson